Novel Fault Detection and Localization Algorithm for Low-Voltage DC Microgrid - Bhargav, Reddipalli; Bhalja, Bhavesh R.; Gupta, Chandra P. (IEEE transactions on industrial informatics, 2020)
Accurate estimation of fault location is highly crucial for swift maintenance and early power restoration. Since faults in dc networks are time critical, this article proposes a new fault detection and localization scheme for a low-voltage direct current (LVdc) microgrid network. Low-resistance faults are detected by observing voltage across the inductor whereas high-resistance ground faults are identified by measuring ground current at the relay location. Thereafter, based on iterative method, fault location is estimated by comparing analytically derived fault current with the measured value of fault current. Genuineness of the suggested technique has been assessed by simulating various internal, external, and simultaneous faults on a typical LVdc microgrid network modeled in power system computer aided design/electromagnetic transients including dc (PSCAD/EMTDC) environment. The proposed method is capable of detecting and locating both low- and high-resistance dc faults without utilizing remote-end quantities. Subsequently, initial guess has minimal impact on the convergence and accuracy of the proposed algorithm. Comparative evaluation of the proposed technique with other techniques clearly proves its superiority in terms of better discrimination against external faults, rapid detection during internal faults, independency on the network topology, and higher accuracy for fault distance estimation against all types of internal faults.